Determinants of the hCG Concentration in the Early Luteal Phase After Final Maturation of Follicles With Bolus Trigger of Recombinant hCG - Vuong, Lan N.; Pham, Toan D.; Ho, Vu N. A.; Ho, Tuong M.; Humaidan, Peter; Andersen, Claus Yding (Frontiers in Endocrinology, 2020)
Introduction: It has recently been shown that late follicular phase progesterone levels correlate well with those in the early luteal phase, and that progesterone levels before and 12 hours after human chorionic gonadotropin (hCG) administration predict levels during the early luteal phase. This study investigated determinants of serum hCG levels after a bolus dose of hCG for triggering ovulation in women undergoing in vitro fertilization (IVF). Materials and Methods: This retrospective analysis was performed on data from a prospective study of women aged 18–42 years with normal ovarian reserve receiving gonadotropin-releasing hormone (GnRH) antagonist co-treatment during ovarian stimulation with follicle-stimulating hormone (FSH) who were followed until 6 days after oocyte pick-up (OPU) in a single IVF cycle. The main outcome measures were early luteal phase serum hCG levels, and predictors of those levels. Results: There was wide inter-individual variability in early phase hCG concentrations over the period from 12 hours after hCG injection up to 6 days after OPU. Patients with serum hCG values in the bottom 10% had a significantly higher body mass index (BMI; p=0.038) and a significantly longer duration of stimulation (p=0.014) than those with higher serum hCG values. Serum progesterone levels up to the first 36 hours after hCG injection were significantly higher in the low versus higher serum hCG group, but were similar at all other time points. There was a significant correlation between serum hCG level after hCG administration and BMI (lower BMI = higher serum hCG). In a cluster analysis, patients with the lowest serum hCG and progesterone levels at 12 hours after hCG injection had significantly higher BMI, and significantly lower anti-Müllerian hormone level, duration of stimulation, and number of follicles of ≥11 and ≥14 mm compared with the other three clusters. Conclusion: Predictors of low serum hCG after a trigger bolus were difficult to determine, but BMI seems to be important. More detailed information on the luteal phase hormonal profile and data on predictors of hormone levels during this critical period can facilitate the development of strategies to allow individualization of the luteal phase support regimen potentially improving IVF outcomes.